The distributional solutions of some systems of linear differential equations - Ligęza, Jan (Annales Mathematicae Silesianae, 1990)
In this paper we prove a theorem on the existence and uniqueness of the solution of the Cauchy problem for linear differential equations with distributional coefficients.